2019
DOI: 10.1177/0973005219836576
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment in Village Governance Transformation in Indonesia: Between Hope and Criticism

Abstract: Since the launch of Law No. 6/2014 regarding villages, scholarly concerns on village studies are growing. However, studies focusing on gender equality in Village Law implementation are still few. This article discusses the responses of the village government to gender problems in their respective areas. Based on field research in two villages in Java, namely Panggungharjo and Lerep, this article recognizes that there is greater attention on gender issues since the implementation of the law. However, village he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
9
0
5
Order By: Relevance
“…Proses pemberdayaan masyarakat desa juga penting untuk memastikan kesetaraan gender (Kristianti, 2020). Perempuan di desa perlu untuk memahami bahwa mereka memiliki hak dan posisi yang sama dengan laki-laki dalam pengambilan keputusan di tingkat desa (Kushandajani & Alfirdaus, 2019).…”
Section: Iii4 Dana Desa Untuk Pemberdayaan Masyarakat Dan Pembangunan Berkelanjutanunclassified
“…Proses pemberdayaan masyarakat desa juga penting untuk memastikan kesetaraan gender (Kristianti, 2020). Perempuan di desa perlu untuk memahami bahwa mereka memiliki hak dan posisi yang sama dengan laki-laki dalam pengambilan keputusan di tingkat desa (Kushandajani & Alfirdaus, 2019).…”
Section: Iii4 Dana Desa Untuk Pemberdayaan Masyarakat Dan Pembangunan Berkelanjutanunclassified
“…Based on the provisions stipulated in Law no. 6 of 2014 concerning villages, villages are the policy of the Indonesian government in terms of village autonomy, namely 1) the village has the authority to allocate village finances, 2) the authority of the village government in improving the economy and welfare of the community, and 3) the village community participates in the development carried out in the village (Kushandajani and Alfirdaus, 2019).…”
Section: Village Governmentmentioning
confidence: 99%
“…A new budgeting system was applied, which made fund allocation for any programmes heavily dependent on the decision-making of local authorities. In the initial studies by Kushandajani and Alfirdaus (2019), it was shown that the responses of the local authorities to gender problems were low, and women empowerment was placed as secondary among the development priorities. The continuity of funding, supervision and legal status of the SPP are now uncertain and need a broader policy framework.…”
Section: Introductionmentioning
confidence: 99%